微波消解-ICP-MS法测定肺癌患者体液和头发中的14种元素的含量 (Zhongguo Fei Ai Za Zhi, 2010)
BACKGROUND AND OBJECTIVE: The trace element contents in the body fluid and hair are the important monitoring indicators for many diseases. The analysis of the trace element contents in the samples of lung cancer patients is helpful to the early diagnosis and treatment effectiveness evaluation to the patients. The aim of this study is to develop an ICPMS method for the determination of Cr, Fe, Mn, Al, Cd, Cu, Zn, Ni, Se, Pb, Ca, Mg, Sr, P in the body fluid and hair of lung cancer patients. METHODS: Samples of body fluid and hair from lung cancer patients were digested with microwave and 14 trace elements were determined with inductively coupled plasma mass spectrometry. RESULTS: GBW09101 standard reference material of human hair was used to validate the accuracy of the established method, and the results indicated that there is no obvious difference between the measured values and the references values. Forty-eight samples from 16 lung cancer patients were analyzed with the established method, and several generalizations were discovered. CONCLUSION: The established method can be used for the multielement simultaneous determination of the samples of lung cancer patients, which are helpful to the diagnosis and treatment of the lung cancer.